Concepts of epidemiology : integrating the ideas, theories, principles, and methods of epidemiology - Bhopal, Raj S. (Oxford, UK : Oxford University Press, 2016)
Epidemiology is a population science that underpins health improvement and health care, by exploring and establishing the pattern, frequency, trends, and causes of a disease. Concepts of Epidemiology comprehensively describes the application of core epidemiological concepts and principles to readers interested in population health research, policy making, health service planning, health promotion, and clinical care.
What is epidemiology? The nature, scope, variables, principal measures, and designs of a biological, clinical, social and ecological science -- The epidemiological concept of population -- Variation in disease by time, place, and person: background and a framework for analysis of genetic and environmental effects -- Error, bias and confounding in epidemiology -- Cause and effect: the epidemiological approach -- Interrelated concepts in the epidemiology of disease: natural history and incubation period, time trends in populations, spectrum, iceberg, and screening -- The concept of risk and fundamental measures of disease frequency: incidence and prevalence -- Summarizing, presenting and interpreting epidemiological data: building on incidence and prevalence -- Epidemiological study designs and principles of data analysis: a conceptually integrated suite of methods and techniques -- Epidemiology in the past, present and the future: theory, ethics, context, and critical appraisal.
Includes bibliographical references and index.
Keywords: Epidemiology; Epidemiologic methods